Upaya Meningkatkan Hasil Belajar Bahasa Indonesia dengan Model Modeling The Way Berbantuan Media Audio Visual pada SDN 5 Telangkah Tahun Pelajaran 2016/2017 - Prestini Prestini; Diplan Diplan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to improve learning outcomes and describe the activities of students in learning Indonesian with the Modeling Model of The Way Unified Audio Visual Media. The method used in this study is a class action. The subjects in this study were all Vb grade students of SDN 5 Telangkah which numbered 35. The results of the study showed that the activities of students became good and learning outcomes increased. This can be seen from the increase in activity, enthusiasm, and enthusiasm of students in participating in the learning process with an average value of 3.37 in the good category. The increase in Indonesian language learning outcomes seen from the initial test averages 61 with classical completeness 37.14% and experienced an increase in the first cycle with the acquisition of indigo scores of 87 students with 91.42% classical completeness in Indonesian subjects especially in drama discipline material.